Effects of Al and Mo on Microstructure and Hardness of As-Cast TNM TiAl Alloys - Gang Yang (MDPI AG, 2021)
The effects of Al and Mo elements on the microstructure and hardness of TNM TiAl alloys (Ti-43.5Al-4Nb-1Mo-0.1B) were studied by decreasing 0.5 at.% Mo and/or increasing 1.5 at.% Al. The results showed that the changed composition of the alloy had a slight influence on the morphology, but had important effects on the volume fraction, size, and composition of each phase. All the alloys had nearly full lamellar (NL) microstructures, with a few βo phases at the boundaries of the colony or in the lamellar colony. The lamellar colony size and the lamellar spacing increased with the decrease in Mo and the increase in Al. The reduction in Mo content reduced the content of each phase in proportion, but the increase in Al content in the alloys led to the corresponding increase in Al content in the α2 and γ phases. The hardness of the alloys decreased with the increase in Al content and the decrease in Mo content. This is mainly due to the increase in lamellar spacing caused by the change in composition. Therefore, the increased content of Al and decreased Mo content are unbeneficial for the microstructure. The relationship between the Vickers hardness and the lamellar spacing obeyed the Hall–Petch relationship.